Klasifikasi Loyalitas Pengguna Data Alumni Pada Forlap Dikti Menggunakan Metode Net Promotore Score - Abdul Fadlil; Rusydi Umar; Fitrah Juliansyah (JURIKOM (Jurnal Riset Komputer), 2022)
As one of the private universities, STMIK Muhammadiyah Jakarta provides electronic-based services to students and alumni using website with the domain address https://pddikti.kemdikbud.go.id. website aims as a means to convey graduation data validation information to alumni in particular by utilizing information technology. The low level of use of the website by alumni in knowing the status of graduation is the background of the need for usability to determine the level of truth of the data and user satisfaction with the website. This study aims to measure the extent to which the website is used by users to achieve its goals. In this study, the test must be carried out using the Net Promoter Score method. So that the results of the NPS calculation will be converted into a percentage that provides information on the extent of loyalty to students in using the Forlap Dikti page to validate alumni data in the STMIK Muhammadiyah Jakarta campus. Then the results obtained from calculations using NPS are: %Promotore - % Dectractor = 53% - 13% = 40. In determining the NPS value is not calculated based on percentages, because NPS calculations are not percentage calculations but integer numbers (consisting of whole numbers) and not contains a fraction or a decimal value